Effects of volar and radial wrist splint for De-Quervain’s Tenosynovitis on pain, dexterity and pinch strength / Faridah Mohammed Ramli - Mohammed Ramli, Faridah (2019)
One of the most common work-related upper limb disorders is De-Quervain Tenosynovitis (DQT). DQT is a painful reaction of the tendons on the thumb side of the wrist. It affects the tendons synovial sheaths of the Abductor Pollicis Longus (APL) and the Extensor Pollicis Brevis (EPB) muscles. This disorder often affects women and people who are 40 years and above. The symptoms include pain on the radial side of the wrist and the persistence of the symptom may affect the ability to engage in daily activities and decreased in occupational performances.